Effects of Environmental Factors on Soluble Expression of a Humanized Anti-TNF-α scFv Antibody in Escherichia coli - Mohammad Sina; Davoud Farajzadeh; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2015)
Purpose: The bacterial cultivation conditions for obtaining anti-TNF-α single chain variable fragment (scFv) antibody as the soluble product in E. coli was investigated. Methods: To avoid the production of inclusion bodies, the effects of lactose, IPTG, incubation time, temperature, shaking protocol, medium additives (Mg+2, sucrose), pH, osmotic and heat shocks were examined. Samples from bacterial growth conditions with promising results of soluble expression of GST-hD2 scFv were affinity purified and quantified by SDS-PAGE and image processing for further evaluation. Results: The results showed that cultivation in LB medium under induction by low concentrations of lactose and incubation at 10 °C led to partial solubilization of the expressed anti-TNF-α scFv (GST-hD2). Other variables which showed promising increase in soluble expression of GST-hD2 were osmotic shock and addition of magnesium chloride. Furthermore, addition of sucrose to medium suppressed the expression of scFv completely. The other finding was that the addition of sorbitol decreased the growth rate of bacteria. Conclusion: It can be concluded that low cultivation temperature in the presence of low amount of inducer under a long incubation time or addition of magnesium chloride are the most effective environmental factors studied for obtaining the maximum solubilization of GST-hD2 recombinant protein.